Incidence, causative drugs, and economic consequences of drug-induced SJS, TEN, and SJS–TEN overlap and potential drug–drug interactions during treatment: a retrospective analysis at an Indonesian referral hospital - Abdulah R; Suwandiman TF; Nadhira H; Destiani DP; Suwantika AA; Barliana MI; Lestari K (Dove Medical Press, 2017)
Rizky Abdulah,1 Tazkia F Suwandiman,1 Nadhira Handayani,1 Dika P Destiani,1 Auliya A Suwantika,1 Melisa I Barliana,2 Keri Lestari1 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, 2Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, Indonesia Background: Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are acute life-threatening adverse drug reactions (ADRs) that are commonly caused by medications. Apart from their contribution to morbidity and mortality, these diseases may also present substantial consequences on health care resources. In this study, we aimed to identify the incidence, causative drugs, and economic consequences of these serious ADRs and potential drug–drug interactions (DDIs) during treatment.Methods: A retrospective study that included 150 patients diagnosed with drug-induced SJS, SJS–TEN overlap, and TEN, from 2009 to 2013 in a referral hospital in West Java Province, Indonesia, was conducted to analyze the causative drugs, cost of illness (COI) as a representation of economic consequences, and potential DDIs during treatment.Results: The results showed that analgesic–antipyretic drugs were the most frequently implicated drugs. The COIs for SJS, SJS–TEN overlap, and TEN patients were 119.49, 139.21, and 162.08 US dollars per day, respectively. Furthermore, potential DDIs with several therapeutic medications and corticosteroids used to treat SJS, SJS–TEN overlap, and TEN were also identified.Conclusion: This study showed that analgesic–antipyretic was the major causative drug which contributed to SJS, SJS–TEN overlap, and TEN. Furthermore, our results also showed that SJS, SJS–TEN overlap, and TEN may cause considerable financial consequences to patients. Keywords: Stevens–Johnson syndrome, toxic epidermal necrolysis, adverse drug reactions, cost of illness